Gibberellin confers to the expression of TaGA-6D and negatively regulates the fertility of wheat with Aegilops juvenalis cytoplasm - He, Mengting (Plant science : an international journal of experimental plant biology, 2023)
Copyright © 2023 Elsevier B.V. All rights reserved.